Spectroscopy and perturbation analysis of the CO A1Π −X1Σ+ (2, 0), (3, 0) and (4, 0) bands. (3rd March 2016) - Niu, M. L.; Salumbides, E. J.; Heays, A. N.; de Oliveira, N.; Field, R. W.; Ubachs, W.
ABSTRACT: The (2, 0) (3, 0) and (4, 0) bands of the A 1 Π −X 1 Σ + system of 12 C 16 O have been re-investigated by high-resolution vacuum ultraviolet absorption spectroscopy. A vacuum ultraviolet Fourier-transform spectrometer, illuminated by synchrotron radiation, was applied to record a jet-cooled spectrum, a room temperature static gas spectrum and a high-temperature (900 K) quasi-static gas spectrum, resulting in absolute accuracies of 0.01−0.02 cm −1 for the rotational line frequencies. Precise laser-based data were included in the analysis allowing for a highly accurate determination of band origins. Rotational levels up to J = 52 were observed. The data were used to perform an improved analysis of the perturbations in the A 1 Π, v = 2, v = 3 and v = 4 levels by vibrational levels of the D 1 Δ, I 1 Σ −, e 3 Σ −, d 3 Δ and a′ 3 Σ + states. Abstract :